A retrospective study on the prevalence of anti-phospholipid antibodies, thrombotic events and cutaneous signs of vasculopathy in 173 hospitalized COVID-19 patients. (31st August 2021) - Gasparini, Giulia; Canepa, Paola; Verdiani, Simonetta; Carmisciano, Luca; Cozzani, Emanuele; De Grazia, Denise; Andrea, Orsi; Icardi, Giancarlo; Parodi, Aurora
Background: Hypercoagulability is a risk factor of thromboembolic events in COVID-19. Anti-phospholipid (aPL) antibodies have been hypothesized to be involved. Typical COVID-19 dermatological manifestations of livedo reticularis and digital ischemia may resemble cutaneous manifestations of anti-phospholipid syndrome (APS). Objectives: To investigate the association between aPL antibodies and thromboembolic events, COVID-19 severity, mortality, and cutaneous manifestations in patients with COVID-19. Methods: aPL antibodies [anti-beta2-glycoprotein-1 (B2GP1) and anti-cardiolipin (aCL) antibodies] were titered in frozen serum samples from hospitalized COVID-19 patients and the patients' clinical records were retrospectively analyzed. Results: 173 patients were enrolled. aPL antibodies were detected in 34.7% of patients, anti-B2GP1 antibodies in 30.1%, and aCL antibodies in 10.4%. Double positivity was observed in 5.2% of patients. Thromboembolic events occurred in 9.8% of patients, including 11 pulmonary embolisms, 1 case of celiac tripod thrombosis, and six arterial ischemic events affecting the cerebral, celiac, splenic, or femoral-popliteal arteries or the aorta. aPL antibodies were found in 52.9% of patients with vascular events, but thromboembolic events were not correlated to aPL antibodies (adjusted OR = 1.69, p = 0.502). Ten patients (5.8%) had cutaneous signs of vasculopathy: nine livedo reticularis and one acrocyanosis. No significant association was observed between the presence of cutaneous vasculopathy and aPL antibodies ( p = 0.692). Conclusions: Anti-phospholipid antibodies cannot be considered responsible for hypercoagulability and thrombotic events in COVID-19 patients. In COVID-19 patients, livedo reticularis and acrocyanosis do not appear to be cutaneous manifestations of APS.